2022
DOI: 10.24057/2071-9388-2021-005
|View full text |Cite
|
Sign up to set email alerts
|

Assessing The Spatiotemporal Urban Green Cover Changes and Their Impact on Land Surface Temperature and Urban Heat Island in Lahore (Pakistan)

Abstract: Urban vegetation has a decisive role in sustaining homogeneous Land Surface Temperature (LST) in a built-up environment. However, urban areas are facing rapid changes in land use/land cover (LULC) over the last few decades as green cover is being replaced by built-up structures. Consequently, LST is increasing and urban heat island (UHI) effects are expanding. In this context, this study was organized to assess urban green cover changes in Lahore and their impact on LST and UHI effects. For this, climate data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The results showed that built-up areas increased by 113.85% and green cover decreased by 392.78 km2 between 1990 and 2020. LST and UHI intensity were found to be positively correlated with built-up areas and negatively correlated with green cover [32].…”
Section: Literature Reviewsmentioning
confidence: 91%
“…The results showed that built-up areas increased by 113.85% and green cover decreased by 392.78 km2 between 1990 and 2020. LST and UHI intensity were found to be positively correlated with built-up areas and negatively correlated with green cover [32].…”
Section: Literature Reviewsmentioning
confidence: 91%
“…The prevalence of UHI is currently increasingly heightened in lockstep with the global temperature increase caused by climate change with the occurrence of successive and intense heat waves as its striking manifestation (Coumou & Robinson, 2013;Oliveira et al, 2022). The escalating UHI leads to elevated energy consumption (Dawodu and Cheshmehzangi, 2017) and compromised environmental quality (Park et al, 2018;Jabbar and Yusoff, 2022). It also exacerbates the vulnerability of urban systems, already in uenced by factors such as land use (LULC), population density, intricate infrastructure systems and diverse economic activities.…”
Section: Introductionmentioning
confidence: 99%
“…These factors encompass the quality and quantity of space, attributes of potential users (age, gender, race, socioeconomic profile), psychological factors (capability, identified hindrance) influencing personal preferences, accessibility, provision of facilities according to needs of users, parks maintenance and safety (Giles-Corti et al 2005). Green areas create a better human environment by controlling the city's climate, cooling temperature and filtering air (Jabbar & Yusoff, 2022a). It has been recognized that green space is a vital source of a sustainable urban environment (Jabbar et al 2021).…”
Section: Introductionmentioning
confidence: 99%